2011
DOI: 10.1111/j.1399-3038.2010.01093.x
|View full text |Cite
|
Sign up to set email alerts
|

Childhood acute urticaria in northern and southern Europe shows a similar epidemiological pattern and significant meteorological influences

Abstract: Acute urticaria (AU) is a common condition that often presents in childhood. Although there is a general perception of cyclic annual trends in AU, no one has tried to identify any seasonal variation on its prevalence and incidence, associate environmental influences and impute geographic, ethnic, or even genetic features that may contribute to its onset. We aimed to analyze the influence of climate and geographic parameters on annual fluctuation of AU cases referred to the Emergency Departments (EDs) of Norwic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 33 publications
5
40
0
1
Order By: Relevance
“…Viruses, such as adenovirus, enterovirus, rotavirus, respiratory syncytial virus, Epstein-Barr virus and cytomegalovirus have been reported to cause acute urticaria in children (8,11,13). Seasonalities of several acute respiratory viral infections and acute urticaria coincide, which underlines the significance of these infections as a potential cause of acute urticaria in children (7,13).…”
Section: Infectionsmentioning
confidence: 94%
See 3 more Smart Citations
“…Viruses, such as adenovirus, enterovirus, rotavirus, respiratory syncytial virus, Epstein-Barr virus and cytomegalovirus have been reported to cause acute urticaria in children (8,11,13). Seasonalities of several acute respiratory viral infections and acute urticaria coincide, which underlines the significance of these infections as a potential cause of acute urticaria in children (7,13).…”
Section: Infectionsmentioning
confidence: 94%
“…In many cases of urticaria, no specific cause is found. Overall, success in identifying a cause in paediatric acute urticaria varies widely in literature, from approximately 20% to 90% (7,8). This is mainly justified by different patient recruitment (e.g.…”
Section: Spontaneous Acute Urticariamentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, the triggering factors we found were similar to those in many studies in the literature. The rate of specifying the triggering factors in urticaria ranges between 12.4% and 17% in different studies (11,19,20). It is very difficult to differentiate etiologic factors in urticaria that occurs after use of medication during acute infection in children.…”
Section: Discussionmentioning
confidence: 99%